Board Diversity and Its Effects on Performance and Risk: A Study in Banking Firms in Indonesia - Maulida Nurul Innayah; Bima Cinintya Pratama; Naelati Tubastuvi (Journal of Accounting and Investment, 2021)
Research aims: This study examines the effect of board diversity on firm performance and risk in Indonesia's banking firms.Design/Methodology/Approach:  The population in this study was the banking industry in Indonesia obtained from the Bloomberg database, OSIRIS database, and company annual reports. The sampling technique used in this study was purposive sampling. The sample in the study consisted of 160 company-years of observation for 40 listed banks in Indonesia. The period of the analysis was from 2014 to 2018.Research findings: The results showed that a woman director had a positive effect on performance. The results also revealed that a woman director had a negative effect on the risk because a woman director could correct bias in important decisions. These results are consistent with resource dependence theory that different types of directors provide additional beneficial resources to the firm. This paper then confirms that in banks, the type of diversity seems to be vital because a more diverse board provides more valuable resources, which should improve firm performance and reduce risk. Otherwise, based on the research data, the small number of foreign directors made their existence not affecting performance and risk.Theoretical contribution /Originality: There is still a lack of previous studies that examined the effect of board diversity on performance and risk, especially regarding the heterogeneity of the directors’ nationality in Indonesia. Based on the explanation, this research is expected to contribute to the knowledge regarding the diversity of directors in Indonesia in managing performance and risk.Practitioner/Policy implication: Based on the empirical evidence, directors' gender diversity had a positive effect on optimizing firm performance and minimizing risk. Thus, the company's policy regarding the diversity of directors can be considered, especially about the existence of a woman director.Research limitation/Implication: This study only took a sample of companies included in the banking industry, so this study's results are not necessarily generalizable to companies with different industry types. This study also looked at the diversity of directors based on the directors' demographic characteristics, namely gender and nationality. Future research may use or add to other types of diversity.